Adolescents' Wellbeing at School: What Helps and What Hinders From Feeling Safe and Satisfied? - Horanicova, Simona; Husarova, Daniela; Madarasova Geckova, Andrea; Lackova Rebicova, Miriama; Sokolova, Lenka; deWinter, Andrea F; Reijneveld, Sijmen (International journal of public health, 2024)
OBJECTIVES: The aim of this qualitative study was to identify the main factors that help and hinder adolescents' wellbeing at school using their perspectives and experiences. METHODS: We used data from 45 adolescents in the first year of high school in Slovakia (mean age = 14.98; 22.2% boys). We obtained the data using 11 semi-structured group interviews conducted in 2020/2021. Participants were selected from three types of high school with regard to graduation system. Data was analysed using consensual qualitative research and thematic analysis. RESULTS: We identified three main themes of factors contributing to their wellbeing at school: 1. School (atmosphere and organisation of life at school, physical environment, threats and the ability of school to deal with issues); 2. Relationships (with peers and teachers, and teachers' behaviour towards them); 3. Myself (own perceived obstacles and resilience resources). CONCLUSION: The organisation of life at school, surroundings, threats and dealing with issues importantly affect adolescents' wellbeing. Therefore, adjustment of physical environment and interpersonal competences of teachers, supporting of resilience resources of adolescents should be targets for interventions and prevention programmes at schools.
Keywords: rozhovory jako téma; Students; Qualitative Research; Female; Interviews as Topic; osobní uspokojení; ženské pohlaví; Adolescent; interpersonální vztahy; Slovakia; lidé; Personal Satisfaction; school; školy; učitelé; wellbeing; Schools; qualitative study; Male; satisfaction; Slovenská republika; Interpersonal Relations; studenti; mužské pohlaví; School Teachers; adolescence; mladiství; kvalitativní výzkum; Humans